PROPOSTA METODOLÓGICA DE ZONEAMENTO AMBIENTAL APLICADA AO MUNICÍPIO DE ANAJATUBA (MA) - Dias, Luiz Jorge Bezerra da Silva (2006)
The Area of Environmental Protection of the Baixada Maranhense is one of the poorest areas economically of the State of Maranhão (Brazil) and lacking with respect to the readiness of information on the municipal districts that compose her. That implicates in a lack of appropriate theoretical-methodological orientation to the perspectives of environmental plannings and of establishment and execution of public politics gone back to the improvement of the conditions of the inhabitants' life. In that sense, a methodological proposal of Environmental Zoning was elaborated applied to the municipal district of Anajatuba (MA), because that space represents a mosaic of the situations physical, ecological and social (in all the senses) of the regional domain in that he/she interferes. They grew recognition studies and of classification of the elements / physical environmental resources (geology, geomorphology), geoecology(typologies of ecosystems) and humans (population evolution). That approach was complemented by the elaboration of the swinging municipal hidrological, which is considered important for sending to the readiness of the waters, in their several compartments, destined to the human provisioning and maintenance of their activities. The crossing of those information indicates which should be the appropriate sustainability strategies for the municipal district.